روح المقاولاتية في المجال الرياضي وأثرها على دفع المشاريع الرياضية - عدنان بن حمودة; بن شريف ياسين (My University, 2024)
‫تهدف‬‫الدراسة‬ ‫الحالية‬ ‫الى‬ ‫التعرف‬ ‫على‬ ‫أثر‬ ‫روح‬ ‫المقاوالتية‬ ‫في‬ ‫المجال‬ ‫الرياضي‬‫على‬ ‫دفع‬ ‫المشاريع‬ ‫الرياضية‬ ‫لدى‬ ‫طلبة‬ ‫الليسانس‬ ‫والماستر‬ ‫تخصص‬ ‫اإلدارة‬‫والتسيير‬ ‫الرياضي‬ ‫بجامعة‬ ‫األغواط‪،‬‬ ‫ومعرفة‬ ‫مستوى‬ ‫روح‬ ‫المقاوالتية‬ ‫لديهم‬ ‫والفروق‬‫بين‬ ‫الطلبة‬ ‫تبعا‬ ‫لمتغير‬ ‫الجنس‬ ‫والسن‬ ‫والمستوى‬ ‫التعليمي‬ ‫والكشف‬ ‫عن‬ ‫التفاعل‬‫بينها‬ ‫‪.‬‬ ‫مكو‬‫نة‬‫من‬ ‫وقد‬‫استخدم‬ ‫الطالب‬ ‫المنهج‬ ‫الوصفي‬ ‫التحليلي‬ ‫‪،‬‬‫على‬ ‫عينة‬ ‫عشوائية‬ ‫ّ‬ ‫(‬‫‪30‬‬‫)‬‫طالبا‬ ‫من‬ ‫جامعة‬ ‫األغواط‪،‬‬ ‫باإلعتماد‬ ‫على‬ ‫مقياس‬ ‫"روح‬ ‫المقاوالتية"‪،‬‬ ‫وكذلك‬ ‫برنامج‬‫)‪(spss‬‬ ‫في‬ ‫تحليل‬ ‫المعطيات‬ ‫المتحصل‬ ‫عليها‬ ‫بعد‬ ‫تطبيق‬ ‫الدراسة‪،‬‬ ‫وقد‬ ‫أظهرت‬‫النتائج‬ ‫ما‬ ‫يلي‪:‬‬ ‫‪-‬‬‫ال‬ ‫توجد‬ ‫فروق‬ ‫ذات‬ ‫داللة‬ ‫إحصائية‬ ‫في‬ ‫روح‬ ‫المقاوالتية‬ ‫لدى‬ ‫طلبة‬ ‫الليسانس‬ ‫والماستر‬‫تخصص‬ ‫اإلدراة‬ ‫والتسيير‬ ‫الرياضي‬ ‫تعزى‬ ‫لمتغير‬ ‫الجنس‪،‬‬ ‫السن‪،‬‬ ‫المستوى‬‫التعليمي‪.‬‬ ‫‪-‬‬‫مستوى‬ ‫روح‬ ‫المقاوالتية‬ ‫لدى‬ ‫طلبة‬ ‫الليسانس‬ ‫والماستر‬ ‫تخصص‬ ‫اإلدارة‬ ‫والتسيير‬‫الرياضي‬ ‫محايد‪.‬‬
The current study aims to identify the impact of the entrepreneurial spirit in the sports field on advancing sports projects for licence and master students Specialization in Sports Administration and Management at the University of Laghouat, and Knowing their level of entrepreneurship and the differences between students according to the variables of gender, age, and educational level, and revealing the interaction between them. The student used the descriptive analytical method on a random sample of (30) students from the University of Laghouat, Based on scale “Entrepreneurial spirit “ and The “SPSS” program also analyzed the data obtained after applying the study, and the results showed the following: - There are no statistically significant differences in the entrepreneurial spirit for licence and master students Specialization in Sports Administration and Managemen due to the variables of gender, age, and educational level. - The level of entrepreneurship for licence and master students Specialization in Sports Administration and Managemen is middle